2016
DOI: 10.1021/acs.nanolett.6b00743
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide Films with Ultrahigh Conductivity as Li-Ion Battery Current Collectors

Abstract: Solution processed, highly conductive films are extremely attractive for a range of electronic devices, especially for printed macroelectronics. For example, replacing heavy, metal-based current collectors with thin, light, flexible, and highly conductive films will further improve the energy density of such devices. Films with two-dimensional building blocks, such as graphene or reduced graphene oxide (RGO) nanosheets, are particularly promising due to their low percolation threshold with a high aspect ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
145
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(150 citation statements)
references
References 46 publications
2
145
2
1
Order By: Relevance
“…e) SEM image of the cross‐section for RGO/LFP electrode. f) Cycle performance of the RGO/LFP electrode at a discharge rate of 5 C, where the operating voltage range was 2.0–4.5 V. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Recent Progress In Flexible Lithium‐ion Batteriesmentioning
confidence: 99%
“…e) SEM image of the cross‐section for RGO/LFP electrode. f) Cycle performance of the RGO/LFP electrode at a discharge rate of 5 C, where the operating voltage range was 2.0–4.5 V. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Recent Progress In Flexible Lithium‐ion Batteriesmentioning
confidence: 99%
“…[53,54] It has been demonstrated that through significantly lowered structural defects, such highly reduced GO (HRGO) products helped bring about significantly enhanced functional properties for chemical energy storage devices such as metal-ion batteries and supercapacitors (SC), when good crystallinity and associated high electric/ thermal conductivity are essential, as is summarized in Table 1. [55][56][57][58][59] In this work, we focus on reviewing recent advances for the production of HRGO and their applications to chemical energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…[74] The thermal-reduced graphene-based materials were widely researched and applied to obtain low-defect graphene for energy storage devices. This led to excellent improvement in electrochemical performance of such devices as Li-ion batteries (LIBs), [55,[75][76][77][78][79][80][81][82][83][84] Li-air batteries, [85][86][87][88] Li-sulfur batteries (LSBs), [89] Na-ion batteries (SIBs), [81,90] Al-ion batteries (AlBs), [47][48][49][50] and SCs. [91] Zhang et al [83] used graphite oxide (GO) and triphenylphosphine (TPP) as carbon and phosphorus sources for synthesizing phosphorus-doped graphene (PG) by thermal annealing reduction (e.g., 1000°C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies devoted to the conductivity of graphene oxide in polymer composites [1][2][3][4][5][6][7][8]. Graphene oxide is a dielectric, but with appropriate treatment its band gap can be decreased to zero [9,10].…”
Section: Introductionmentioning
confidence: 99%